The effects of foreign direct investment on the host country - Cristina Ioana Antik (Agora International Journal of Economical Sciences (AIJES), 2021)
A corresponds to any flow of foreign direct investment (including loans) granted to foreign companies, provided that residents investing country (in general - enterprise) have an important part of this business property. It is distinguished from short baths capital movements. Direct investment involves mobilization of capital transferred abroad. For this reason, the national statistical departments groups, often under the term direct investment, purchases of shares and long-term loans to the same group of companies that contribute to the industrial capital of the lending company, ie its production capacity.
Keywords: 330